RESPIRATORY SYMPTOMS, LUNG FUNCTION IMPAIRMENT, AND CHRONIC RESPIRATORY DISEASES AMONG CROP FARMERS: ASSESSMENT BY JOB EXPOSURE MATRICES - Sasho Stoleski; Jordan Minov; Jovanka Karadzinska-Bislimovska; Dragan Mijakoski (European Medical Group LTD, 2016)
Objective: To evaluate the prevalence of chronic respiratory symptoms, lung function impairment, and chronic obstructive respiratory diseases in crop farmers. Our objective is to then examine their relation to exposure duration, and to explore the usefulness of job exposure matrices as tools for exposure assessment, and predictors for respiratory health impairment. Methods: A cross-sectional study was performed, including 50 males (mean age: 45.4±10.7 years) employed as crop farmers (duration of exposure: 21.6±9.7 years) and 50 male office workers as a control group (mean age: 44.1±9.8 years) matched for age, smoking habits, and socioeconomic status. Methods of evaluating examined subjects included the completion of a questionnaire on respiratory symptoms in the last 12 months (cough, phlegm, dyspnoea, wheezing, chest tightness, and nasal symptoms), spirometry and histamine challenge (provocative concentration producing a 20% fall in forced expiratory volume in 1 second [FEV1]: ≤8 mg/mL), as well as use of job exposure matrices. Results: Crop farmers had a significantly higher prevalence of cough (29.4%), phlegm (16.7%), and wheezing (11.9%), than the control group (p<0.05). All spirometric parameters (forced vital capacity [FVC], FEV1, FEV1/FVC%, maximal expiratory flow (MEF) at 75%, 50%, and 25%) were lower in crop farmers compared to the control patients, but statistical significance was confirmed only for MEF at 25%, 50%, and 25–75% (p=0.021, p=0.011, and p=0.003, respectively). The prevalence of bronchial hyperresponsiveness, asthma, and chronic obstructive pulmonary disease was higher in crop farmers but without statistical significance. JEM were useful tools for exposure assessment and predictors of factors for asthma and COPD development. Conclusion: The results suggest that occupational exposure among crop farmers is associated with a higher prevalence of respiratory symptoms, lung function impairment, and a higher prevalence of chronic respiratory diseases.
Keywords: respiratory symptoms; farming; lung function; asthma; chronic obstructive pulmonary disease (COPD); job exposure